COFDM System: Overview - Farhan, Mhnd (Indonesian Journal of Engineering and Technology (INAJET), 2023)
This article compares the performance of two modulation techniques—quadrature phase shift keying (QPSK) and quadrature M-ARY AMPLITUDE MODULATION (M-QAM) with M=8, 16, 32, and 64 in a coded orthogonal frequency division multiplexing system. As an error correction code, convolutional technology is used. Vehicle channels with white gaussian noise (AWGN) additives are used for communication. According to simulation data, for QPSK and M-QAM, coded orthogonal frequency division multiplexing systems perform better than uncoded ones. In addition, the system performs better with QPSK than with M-QAM. In addition, when M rises, performance decreases. Keywords: COFDM, M-QAM, QPSK, AWGN